Marketing information products and services in the public sector universities of Khyber Pakhtunkhwa, Pakistan - Muhammad Ismail , Abid Hussain, Muhammad Idrees (IJoLIS, 2023)
Purpose: The aim of this study was to examine the attitude oflibrarians and information professionals towards marketing and to know how the concept of marketing is applied in practice to the university libraries of Khyber Pakhtunkhwa (KP), Pakistan. Design/methodology/approach: The study is based on a survey questionnaire. Total population of the study is consisted of 110 library professionals of the fifteen public sector universities of KP. The target population is consisted of all the information professionals who had at least a postgraduate degree in library and information science.